A randomized, double-blinded, placebo-controlled, crossover study of the HCN channel blocker ivabradine in a capsaicin-induced pain model in healthy volunteers - Tanaka, Satoshi; Ishida, Takashi; Ishida, Kumiko; Fuseya, Satoshi; Ito, Mariko; Sakamoto, Akiyuki; Kawamata, Mikito (Scientific reports, 2022)
Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels have been focused on as a potential therapeutic target for inflammatory and neuropathic pain in rodent models. However, roles of HCN channels in human pain states have been scarcely investigated. We evaluated analgesic effects of 2-day administration of ivabradine, the only clinically available HCN channel blocker, on a capsaicin pain model in a randomized, double-blinded, placebo-controlled, crossover study. Twenty healthy adult subjects (18 males, 2 females) received ivabradine (5–7.5 mg) or a placebo 3 times in 2 days. Then capsaicin (0.5%) was topically applied on the volar forearm for 30 min. The primary outcome was capsaicin-induced spontaneous pain. The secondary outcomes included heat-pain threshold (HPT), flare size, and areas of secondary punctate mechanical hyperalgesia (PMH) and secondary dynamic mechanical allodynia (DMA). There was no significant difference in spontaneous pain ( p = 0.7479), HPT ( p = 0.7501), area of PMH ( p = 0.1052) or flare size ( p = 0.5650) at 30 min after capsaicin application between the groups. In contrast, the area of DMA in the ivabradine group was significantly smaller ( p < 0.001) than that in the placebo group. HCN channels may be differentially involved in the various pain signal transmission pathways in humans.